MiR-33 Silencing Reprograms the Immune Cell Landscape in Atherosclerotic Plaques. Issue 8 (17th February 2021) - Afonso, Milessa Silva; Sharma, Monika; Schlegel, Martin; van Solingen, Coen; Koelwyn, Graeme J.; Shanley, Lianne C.; Beckett, Lauren; Peled, Daniel; Rahman, Karishma; Giannarelli, Chiara; Li, Huilin; Brown, Emily J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: MicroRNA-33 (miR-33 [post-transcriptionally in the rationale]) post-transcriptionally represses genes involved in lipid metabolism and energy homeostasis. Targeted inhibition of miR-33 increases plasma HDL (high-density lipoprotein) cholesterol and promotes atherosclerosis regression, in part, by enhancing reverse cholesterol transport and dampening plaque inflammation. However, how miR-33 reshapes the immune microenvironment of plaques remains poorly understood. Objective: To define how miR-33 inhibition alters the dynamic balance and transcriptional landscape of immune cells in atherosclerotic plaques. Methods and Results: We used single-cell RNA-sequencing of aortic CD45 + cells, combined with immunohistologic, morphometric, and flow cytometric analyses to define the changes in plaque immune cell composition, gene expression, and function following miR-33 inhibition. We report that anti–miR-33 treatment of Ldlr –/– mice with advanced atherosclerosis reduced plaque burden and altered the plaque immune cell landscape by shifting the balance of proatherosclerotic and antiatherosclerotic macrophage and T-cell subsets. By quantifying the kinetic processes that determine plaque macrophage burden, we found that anti–miR-33 reduced levels of circulating monocytes and splenic myeloid progenitors, decreased macrophage proliferation and retention, and promoted macrophage attrition by apoptosis and efferocytotic clearance. Single-cell RNA-sequencing of aortic arch plaques showed that anti–miR-33 reduced the frequency of MHCII hi (major histocompatibility complex II) inflammatory and Trem2 hi (Triggering Receptor Expressed On Myeloid Cells 2) metabolic macrophages, but not tissue-resident macrophages. Furthermore, anti–miR-33 led to derepression of distinct miR-33 target genes in the different macrophage subsets: in resident and Trem2 hi macrophages, anti–miR-33 relieved repression of miR-33 target genes involved in lipid metabolism (eg, Abca1, Ncoa1, Ncoa2, Crot ), whereas in MHCII hi macrophages, anti–miR-33 upregulated target genes involved in chromatin remodeling and transcriptional regulation. Anti–miR-33 also reduced the accumulation of aortic CD8+ T cells and CD4+ T-helper 1 cells, and increased levels of FoxP3+ (Forkhead Box P3) regulatory T cells in plaques, consistent with an immune-dampening effect on plaque inflammation. Conclusions: Our results provide insight into the immune mechanisms and cellular players that execute anti–miR-33's atheroprotective actions in the plaque.